Assessment of toxicity in the freshwater tadpole Polypedates maculatus exposed to silver and zinc oxide nanoparticles: A multi-biomarker approach. (April 2022) - Murthy, Meesala Krishna; Mohanty, Chandra Sekhar; Swain, Priyabrata; Pattanayak, Rojalin
Abstract: Nanoparticles (NPs), especially silver nanoparticles (Ag NPs) and zinc oxide nanoparticles (ZnO NPs), are widely used in various industrial applications and are released into the surrounding environment through industrial and household wastewater. They have enormous toxic effects on aquatic animals and amphibians. In the current study, a multi-biomarker approach was used to assess toxicity on Polypedates maculatus ( P. maculatus ) tadpoles collected from a freshwater pond and exposed to sub-lethal concentrations of Ag-NPs (1, 5 and 10 mg L −1 ) and ZnO-NPs (1, 10 and 50 mg L −1 ). A significant bioaccumulation of silver (Ag) and Zinc (Zn) was observed in the blood, liver, kidney and bones in comparison to control tadpoles. Blood parameters (Red blood cells (RBC), Hematocrit (Htc), White blood cells (WBC), monocytes, lymphocytes and neutrophils), immunological markers (ACH50, lysozyme, total Ig, total protein, albumin, and globulin), biochemical markers (glucose, cortisol, cholesterol, triglycerides, alanine transaminase (ALT), asparatate transaminase (AST), alkaline phosphatase (ALP), urea and creatinine) and the oxidative stress marker (LPO) of serum were increased significantly (p < 0.05) in Ag/ZnO-NPs exposed groups when compared to the control groups. The levels of mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC), mean corpuscular volume (MCV) and haemoglobin (Hb) in the ZnO NP-exposed groups were significantly different from those in the control group. Antioxidant (SOD and CAT) levels were significantly declined in the treatment groups. Based on the results, Ag/ZnO-NPs are toxic to aquatic organisms and amphibians at sub-lethal concentrations. The species P. maculatus can be used as a bioindicator for the nanomaterial (NM) contamination of freshwater systems. Graphical abstract: Image 1 Highlights: The study evaluated the toxic effects of Ag/ZnO-NPs on P. maculatus tadpoles. Exposure to Ag/ZnO-NPs caused morphological abnormalities in tadpoles. Blood profiles are impaired by sub-lethal concentrations of Ag/ZnO-NP exposure. Exposure groups showed impaired antioxidant and biochemical parameters. Exposure groups showed alterations in immunological and metabolic processes.